Pemanfaatan Greenhouse Sebagai Potensi Desa Meningkatkan Produktivitas Pertanian Dan Kesejahteraan Masyarakat (Studi Kasus Desa Kedung Banteng Sukorejo Ponorogo) - Alwi Musyafa Zain; Maulida Agustina Hidayatul Wahidah; Khoirul Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research is the result of a community service activity conducted in Kedung Banteng Village, Sukorejo District, Ponorogo Regency, focusing on the utilization of greenhouse technology to enhance agricultural productivity and local community welfare. The study involved interviews with Mr. Jailani, a senior farmer who has successfully implemented greenhouse technology for melon cultivation in Kedung Banteng Village. The methodology employed is descriptive qualitative, with data collection through direct observation, in-depth interviews, and documentation analysis. The findings indicate that greenhouse technology enables optimal environmental control, such as temperature, humidity, and lighting, allowing plants to grow optimally throughout the year without being affected by external weather changes. The application of this technology not only improves melon yield in terms of quantity and quality but also positively impacts the local economy. Farmers' incomes have increased, and the technology has created new job opportunities in the village. The research also identifies several challenges, such as the high initial investment required and the need for farmer training. Therefore, the importance of cooperation between the government, private sector, and community is crucial to overcoming these challenges. The findings from this community service are expected to serve as a model for sustainable agricultural development and improvement of welfare in other rural areas. This research is the result of a community service activity conducted in Kedung Banteng Village, Sukorejo District, Ponorogo Regency, focusing on the utilization of greenhouse technology to enhance agricultural productivity and local community welfare. The study involved interviews with Mr. Jailani, a senior farmer who has successfully implemented greenhouse technology for melon cultivation in Kedung Banteng Village. The methodology employed is descriptive qualitative, with data collection through direct observation, in-depth interviews, and documentation analysis. The findings indicate that greenhouse technology enables optimal environmental control, such as temperature, humidity, and lighting, allowing plants to grow optimally throughout the year without being affected by external weather changes. The application of this technology not only improves melon yield in terms of quantity and quality but also positively impacts the local economy. Farmers' incomes have increased, and the technology has created new job opportunities in the village. The research also identifies several challenges, such as the high initial investment required and the need for farmer training. Therefore, the importance of cooperation between the government, private sector, and community is crucial to overcoming these challenges. The findings from this community service are expected to serve as a model for sustainable agricultural development and improvement of welfare in other rural areas.